Industrial Training Report: Shared Facilities Library Pagoh Higher Education Hub / Muhammad Salihin Rashid - Rashid, Muhammad Salihin (Faculty of Information Management, 2019)
This paper was produced to fulfil the requirement of a course named IMC 690, Industrial Training which are compulsory course for students before finishing their Bachelor of Science in Information Studies (Hons.) Library and Information Management. This paper reports the task that had been done, activities, special project and lesson learned for 5 months industrial training at Shared Facilities Library, Pagoh Higher Education, Muar, Johor. There are also background, services, facilities and collection of PSB that included in the report. Based on the industrial training, some limitations and recommendations have been proposed in order to help the organization to improve its services for the upcoming years. In this report, readers can take a look at all the activities and program have been done during the industrial training and it can apply to all other future students to overview this course furthermore.